The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/2040622319889259
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular electrical stimulation-enhanced rehabilitation is associated with not only motor but also somatosensory cortical plasticity in chronic stroke patients: an interventional study

Abstract: Background:Somatosensory function has been frequently overlooked in clinics and research in the field of chronic stroke. The effects of neurorehabilitation interventions on sensory processing have still to be investigated using electrophysiological means.This study investigated the effect of hybrid assistive neuromuscular dynamic stimulation (HANDS) therapy utilizing closed-loop electromyography-controlled neuromuscular electrical stimulation (NMES), on sensory changes and cortical plasticity among patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 56 publications
0
27
0
1
Order By: Relevance
“…They also mentioned that there was some evidence to support the use of passive sensory techniques for improving sensation and sensorimotor function. Regarding the UE of patients with chronic stroke, not much evidence has been reported, but Byl et al reported that their sensorimotor training improved both sensory and motor functions ( 54 ), and Tashiro et al showed improvement in the TLT and somatosensory evoked potentials, in addition to motor function, after intervention with neuromuscular electrical stimulation ( 55 ). The patients can successfully proceed to receiving such rehabilitation if their somatosensory deficits are properly identified.…”
Section: Discussionmentioning
confidence: 99%
“…They also mentioned that there was some evidence to support the use of passive sensory techniques for improving sensation and sensorimotor function. Regarding the UE of patients with chronic stroke, not much evidence has been reported, but Byl et al reported that their sensorimotor training improved both sensory and motor functions ( 54 ), and Tashiro et al showed improvement in the TLT and somatosensory evoked potentials, in addition to motor function, after intervention with neuromuscular electrical stimulation ( 55 ). The patients can successfully proceed to receiving such rehabilitation if their somatosensory deficits are properly identified.…”
Section: Discussionmentioning
confidence: 99%
“… 77 , 78 Broadening the scope of clinical assessment to include multiple aspects of proprioception is likely to broaden the scope of investigation of treatment strategies. For example, recent studies using somatosensory stimulation (mostly neuromuscular electrical stimulation) 79 , 80 to provide increased proprioceptive input show promising results in people after stroke. Improvements are thought to be due, in part, to the reintegration of the internal representations of the stimulated body parts.…”
Section: Discussionmentioning
confidence: 99%
“…In study by Pope it was shown that proprioceptive input from the neck also may change cerebellar output affecting M1 plasticity [59]. In the study of Vidoni and colleagues preserved motor learning after stroke was related to the degree of proprioceptive deficit suggesting the relation between proprioceptive perception from muscle spindles and motor learning and central neuroplasticity [58,60].…”
Section: Neurologic Correlationmentioning
confidence: 99%
“…Many patients with stroke Proprioception and Clinical Correlation DOI: http://dx.doi.org/10.5772/intechopen.95866 experience proprioceptive deficits. Recovery of proprioception increases in the chronic phase [57,58]. In study by Pope it was shown that proprioceptive input from the neck also may change cerebellar output affecting M1 plasticity [59].…”
Section: Neurologic Correlationmentioning
confidence: 99%